2017
DOI: 10.3791/53639
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Communication for People with Disorders of Consciousness

Abstract: In this experiment, we demonstrate a suite of hybrid Brain-Computer Interface (BCI)-based paradigms that are designed for two applications: assessing the level of consciousness of people unable to provide motor response and, in a second stage, establishing a communication channel for these people that enables them to answer questions with either 'yes' or 'no'. The suite of paradigms is designed to test basic responses in the first step and to continue to more comprehensive tasks if the first tests are successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Results showed that the users preferred background music to the canonical approach (no background music) without significant changes in BCI performance. While auditory BCIs have been validated in prior work (Hill et al, 2004 ; Kübler et al, 2009 ; Treder et al, 2014 ; Lesenfants et al, 2016 ; Ortner et al, accepted ), this outcome suggests that future auditory, and perhaps other, BCIs could improve user satisfaction by incorporating background music. Further work is needed to explore issues such as: the best signal processing methods and classifiers; performance with target patients at different locations; improving performance with inefficient subjects; and different types of auditory stimuli and background music, including music chosen based on each subject's mental state (Tseng et al, 2015 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Results showed that the users preferred background music to the canonical approach (no background music) without significant changes in BCI performance. While auditory BCIs have been validated in prior work (Hill et al, 2004 ; Kübler et al, 2009 ; Treder et al, 2014 ; Lesenfants et al, 2016 ; Ortner et al, accepted ), this outcome suggests that future auditory, and perhaps other, BCIs could improve user satisfaction by incorporating background music. Further work is needed to explore issues such as: the best signal processing methods and classifiers; performance with target patients at different locations; improving performance with inefficient subjects; and different types of auditory stimuli and background music, including music chosen based on each subject's mental state (Tseng et al, 2015 ).…”
Section: Discussionmentioning
confidence: 96%
“…Several groups have shown that an auditory P300 BCI could serve as a communication channel for severely paralyzed patients, including persons diagnosed with DOC. Indeed, DOC patients could also benefit from BCI technology to assess cognitive function (Risetti et al, 2013 ; Lesenfants et al, 2016 ; Käthner et al, 2013 ; Edlinger et al, 2015 ; Ortner et al, accepted ). Since many DOC patients cannot see, and have very limited means for communication and control, they have a particular need for improved auditory BCIs.…”
Section: Introductionmentioning
confidence: 99%
“…To date, experiments with cognitive BCIs have focused on improving memory, attention, and consciousness ( Bamdad et al, 2015 ; Burke et al, 2015a ; deBettencourt et al, 2015 ; Luauté et al, 2015 ; Ezzyat et al, 2017 , 2018 ; Jiang et al, 2017 ; Ortner et al, 2017 ; Kucewicz et al, 2018 ). Burke et al (2015a) attempted an initial memory BCI system using theta (4–8 Hz) and alpha (9–14 Hz) band spectral activity to trigger the optimal timing of object presentation during memory encoding.…”
Section: Current Advancesmentioning
confidence: 99%
“…However, recent studies demonstrate that short bursts of lateral temporal cortex stimulation delivered only during poor encoding states are associated with a disruption of the innate spectral activity and an improvement in memory performance ( Ezzyat et al, 2018 ; Kucewicz et al, 2018 ). In non-memory cognitive systems, control signals utilizing blood-oxygen-level dependent (BOLD), evoked potentials, or spectral analysis have been incorporated as biofeedback therapy for self-optimization of attentional networks ( deBettencourt et al, 2015 ; Jiang et al, 2017 ) and as communicative tools for patients with altered levels of consciousness ( Luauté et al, 2015 ; Ortner et al, 2017 ). These approaches have also been used to assess and predict the depth of cognitive processing, reflected by the level of task difficulty, in memory, language, and visual task domains ( Nicolae et al, 2017 ).…”
Section: Current Advancesmentioning
confidence: 99%
See 1 more Smart Citation